Peran Digital Banking Dalam Meningkatkan Akurasi Dan Efektivitas Alokasi Dana Bank: The Role of Digital Banking in Improving the Accuracy and Effectiveness of Bank Fund Allocation - Dui Rofifah Dzahabiyyah Dzahabiyyah; Tiara Afrilia Putri; Bagas Khoro Pratama; Putri Nuraini (Jurnal Keuangan dan Perbankan Syariah, 2026)
Purpose: This article aims to examine the role of Digital banking in improving the accuracy and effectiveness of bank fund allocation and identify factors influencing the optimization of its utilization, both in conventional and Islamic banks. Design/methodology/approach: The research method used is a qualitative approach with a literature review of various literature sources including national scientific journals, reference books, and relevant publications published in the 2020–2025 period.    Research Findings: The results of the study indicate that Digital banking plays a significant role in improving the accuracy of fund allocation through technology-based data analysis, efficiency of the fund distribution process, increased transparency and supervision, more accurate liquidity management, and data-driven decision-making. Contribution/Originality/Novelty: In the context of Islamic banking, Digital banking also supports compliance with Islamic principles through transparent contract recording, real-time financing monitoring, and strengthening the Islamic supervisory function. However, the implementation of Digital banking still faces challenges in terms of data quality, system security, human resource readiness, and technological infrastructure gaps. Therefore, optimizing Digital banking requires policy support, increased human resource capacity, and strengthened governance and oversight to sustainably improve the accuracy and effectiveness of fund allocation.